Isolation of cfDNA from spent culture media and its association with implantation rate and maternal immunomodulation - Amin Alizadegan; Maryam Akbarzadeh; Mohammad Sadegh Soltani-Zangbar; Roshanak Sambrani; Kobra Hamdi; Alieh Ghasemzadeh; Parvin Hakimi; Behnam Vahabzadeh; Hassan Dianat-Moghadam; Amir Mehdizadeh; Sina Mohammadinejad; Sanam Dolati; et al. (BMC Research Notes, 2022)
Abstract Objectives This investigation aims to evaluate the association between the concentration of cell-free DNA (cfDNA) in the spent culture medium (SCM) with implantation rate and the maternal immune system in the invitro fertilization (IVF). In this study, 30 embryos were cultured and scored according to Gardner's criteria. SCM was gathered on day five from every embryo to analyze the quantity of cfDNA. The real-time PCR technique evaluated the expression level of transcription factors, including Foxp3, RORγt, GATA3, and T-bet. The percentage of Th1, Th2, Th17, Treg, NK cells, and NK cells cytotoxicity was evaluated by flow cytometry. Results The concentration of cfDNA in the β-HCG (-), β-HCG ( +), and ongoing pregnancy groups were 20.70 ± 9.224 ng/µL, 27.97 ± 7.990 ng/µL, and 28.91 ± 8.566 ng/µL, respectively. The ratio of Th1/Th2 and Th17/Treg reduced significantly in pregnant women, as well as the level of NK cells and NK cytotoxicity cells fell dramatically in the ongoing pregnancy group. The expression level of RORγt and T-bet declined while the expression level of Foxp3 and GATA3 increased considerably in pregnant mothers. Our investigation revealed that the concentration level of cfDNA in SCM could not be associated with implantation rate, prediction of ongoing pregnancy, and maternal immune system.